"I ain't gonna work on Maggie's farm no more": the five ordoliberal critiques of capitalism. (4th July 2022) - Nedergaard, Peter
ABSTRACT: These days, economic liberalism and international capitalism are typically presented as two sides of the same coin. Therefore, when discussing the downsides of capitalism, the critique usually stems from a socialist and thus "outside" perspective. However, a distinct – and historically overlooked – critique of capitalism comes from the inside of liberalism, namely from the so-called ordoliberalism. This is a German variant of liberalism from the 1930s and 1940s, and it may come as a surprise to some that it actually has a lot to offer in the present-day discussion of capitalism. This article reconstructs the ordoliberal critique and argues that ordoliberalism presents a strong and coherent critique of capitalism. In my reconstruction of ordoliberalism, I divide the critique into five categories (methodological, anthropological, moral, monopolistic, and strategic) and show that these five forms are bound together and underpin each other. Above all, this means that the connection between economic liberalism and capitalism is not as close as otherwise assumed.